Design and development of mechanical rabbit cage - Nazrith, Zulkafli (2008)
The study of manufacturing was very important in order to carry out this project to ensure that the student understand on what are needs to do. This project is about designing and fabricating the Mechanical Rabbit Cage to solve problems that most user encounter while keep their love rabbit. This project will ease the user while use it because of it ease to use and ease to clean ability. This project involves designing the rabbit cage by searching in the internet and on local hardware shop. With combine the idea from internet and refer to problem solving, this product design is a new idea. After completing design process, it is made real product by many manufacturing method. This project also require to ensure the safety for the indeed of publishing. Methods and process involve in this project for instance joining using MIG and arc welding, cutting using shearing method and a finishing processes. This project in mainly about generating a new concept of rabbit cage for outdoor use that can protect the rabbit and ease to handling. After all process had been done, this cage may help user to understand the fabrication and designing process that involved in this project.